Management of lymphedema and pleural efusion in patients with breast cancer stadium IV: a case study - Novriyanti, Sukma; Effendy, Christantie; Fitriana, Nazula (Journal of health research and technology, 2023)
Background: Metastasis of breast cancer to distant organs occurs as a result of cancer cells spreading through the lymphatic system or blood flow. Pleural effusion and lymphedema are manifestations due to metastasis of cancer cells. Management is needed to relieve suffering, reduce complications, and improve quality of life. Methods: Case study was conducted using observation, interviews, physical examination, and tracing of patient medical records. Informed consents were given before the case study started. Case: Mrs. S, 67 years old, was diagnosed with breast cancer in 2021. The patient was only treated with herbal treatment before being admitted to the hospital in June 2022 with shortness of breath which later found metastases to the lungs. Clinical findings include pitting edema in the right upper extremity, pleural effusion, ulcer cancer from the breast to the right armpit, and a closed fracture of the right clavicle. Swelling in the right arm has occurred since March 2022 slowly spreading throughout the arm. The patient is on bed rest in a semi-fowler's position, limited range of motion, and all activities are assisted by the family. Intervention: The patient is given oxygen therapy with nasal cannula 3lpm and 30o semi-fowler positioning. Skin care intervention is used to treat lymphedema problem. Patient’s family also received education to prevent and reduce the occurrence of swelling in the contralateral arm. Conclusion: Shortness of breath management with oxygen therapy and positioning can help facilitate adequate breathing along with drainage of pleural fluid. Treatment of lymphedema focuses on reducing swelling and minimizing complications. Treatment options are adjusted to the patient's clinical condition.